Histone modifications and prospects for an epigenetic code - Turner, Bryan (Henry Stewart Talks, 2007)
Enzyme-catalyzed modification of the N-terminal tail domains of core histones provides an array of marks across the nucleosome surface and a source of epigenetic information, this information influences protein-protein interactions during short-term regulation of ongoing transcription and is a means of maintaining or modifying patterns of gene expression from one cell generation to the next, cellular memory, histone modifications may constitute a heritable epigenetic code that acts in concert with the genetic code as a long-term regulator of gene expression
Reviewed at 2015/01/19